Cultural Exchange in Southern France: Archaeological and Textual Evidence for the Celto-Ligurian Tribe of the Salluvii. - Donohue, Shannon. (2017)
Abstract: The south of France presents a valuable case in the study of the cultural contact and exchange between the Greeks and indigenous non-Greek peoples with whom they came in contact. This study concentrates on the material culture of the Salluvian sites of Entremont and Glanum, with the purpose of showing that the Salluvian elite were receptive to Greek technological innovations. Early scholarship in the 1940's characterized Glanum and Entremont differently, arguing that Glanum was a Greek site and Entremont a Salluvian site. Taking account of recent scholarly debate over their interpretation, this study will show that both of these sites were the result of Salluvian efforts. The evidence from Glanum and Entremont suggests that the elite members of the Salluvii took on modern Hellenistic cultural elements of art and architecture in order to demonstrate the prosperity of their community, which resulted in Salluvian sites that exhibited Greek features.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Classics.; Advisor: R. Bruce Hitchner.; Committee: J. Matthew Harrington, and David Proctor.; Keyword: Archaeology.